My Son The Fanatic, de Hanif Kureishi, ou l’intégration à rebours - Jean-Paul Révauger (Cahiers du MIMMOC)
Using films, or, for that matter, any cultural artefact in order to reach an understanding of social issues raises a number of methodological difficulties. Films do not “reflect” reality. Creative works, even when they claim to be realistic, have a strong but indirect relationship with the context in which they were produced. Many factors interfere: the context, the author, a real person endowed with ideas and values – Bourdieu’s “habitus”- , the dominant techniques and fashions of the time, and, last but not least, the strategy of the author vis a vis other artists. As reception theorists have shown, audiences will respond in widely different manners. My Son The Fanatic will be seen a satanic piece of work by Muslim, and no doubt Christian fundamentalists. Romantic young ladies, who seem to be the target audience of the film’s commercials, will react somewhat differently. The supports of integration will love the criticism of fundamentalists, as will Huntington’s enthusiasts, who seen the civilisation clash as inevitable. The supporters of yesterday’s multicultural and communitarian policies will see it as politically incorrect and “islamophobic”. Hanif Hureishi fans will find the expected plea for individual freedom, and in particular sexual freedom, but might find the demonstration slightly didactic. Indeed, this is vintage Kureishi, since he wrote both the short story and the scenario.